Comparative analysis of the chemical composition of selected face moisturizing creams from drugstore, pharmacy and shop with natural cosmetics - Ewa Żurawska-Płaksej; Aleksandra Śmietańska; Paulina Opalska; Blanka Prałat; Piotr Jasiulewicz; Jakub Obara; Małgorzata Zagrobelna; Anna Bizoń (Polish Pharmaceutical Society, 2022)
Introduction: Cosmetic products for face care contain a number of chemicals which are applied to the skin every day. Despite the restrictive law regulations in Poland and the European Union, guaranteeing the safety of these products, there are still cases of adverse effects related to the use of cosmetics. Aim: Due to the growing interest of consumers in dermocosmetics and natural cosmetics, a comparative analysis of the ingredients in selected moisturizing face creams was performed. Materials and methods: The evaluation covered 30 moisturizing face creams available in drugstores, pharmacies and shops with natural products, classified as drugstore cosmetics, dermocosmetics and natural cosmetics, respectively. Results: Drugstore cosmetics had the widest range of ingredients and contained the most controversial substances, especially in the aspect of the used preservatives (imidazolidine urea, alcohol denaturated). Dermocosmetics were the group among with the highest number of products without potentially allergic fragrances and they also contained a lot of parafin-based emollients, which is beneficial for sensitive and atopic skin. However, the presence of potentially irritating substances (phenoxyethanol, polyethylene glycols) was also found. Natural cosmetics were mostly characterized by the presence of high-quality ingredients (herbal oils and extracts), but there were also products containing potentially irritating substances (limonene, linalool, citronellol, geraniol, phenoxyethanol and pentylene glycol). Conclusions: The chemical composition of cosmetics is of key importance in choosing the adequate product. Reliable information on individual ingredients coming from scientific sources is necessary to correctly assess their safety and identify the role played in the cosmetic product, which enables the verification of marketing declarations used by manufacturers. More efforts are needed to increase consumer awareness of exposure to substances derived from cosmetics.